(untitled) (Jurnal Ilmiah Psikologi MIND SET, 2024)
The increase of elderly population in Indonesia is also accompanied by an increase in the level of loneliness in the elderly. The feeling of loneliness experienced by the elderly cannot be separated from the role of the family. This study aimed to examine the relationship between family functioning and loneliness in the elderly. This research was a quantitative research with a correlational design. The measurement tool used to measure family functioning in this study is the General Functioning Family Assessment Device (α=0,81). While the measurement tool used to measure loneliness in this study is the UCLA Loneliness Scale version 3 (α=0,87). The sample of this study were 100 elderly who live in Jabodetabek who were recruited through snowball sampling. In this study it was also found that there are differences in loneliness in the elderly based on community participation and work status.